Internet banking - Waite, Kathryn (Henry Stewart Talks, 2008)
Exploration of the factors facilitating and hindering adoption of internet banking, Examination of patterns of use and characteristics of users of internet banking, Theories relating to the use of self service technology and innovation diffusion